Numerical Study of the Erosion Distribution of Sulfur-Containing Particulate Gas in 90-Degree Gathering Elbow - Runhua Zhu; Hongming Ren; Qiang Fang; Yang Ren; Dong Jiang; Yongliang Liu; Shudong Liu; Chengyong Li; Danni Tang (Energies, 2023)
The phenomenon of pipeline erosion dominated by sulfur particles has become a key research target for sulfur-containing gas-gathering pipelines. Gas-solid two-phase flow of sulfur-containing gases is simulated with a coupled CFD-DPM model in this paper. The Realizable k-ε turbulence model was used to determine the changes in the complex flow field and the Euler-Lagrange method was used to describe the specific trajectory of sulfur particles in the complex flow field. The main erosion trace distribution and the effect of secondary flow effects at the elbow were analyzed and the erosion distribution pattern was investigated for different curvature ratios, particle sizes, and pipe diameters. The results show that the formation of erosion along the tip of the V-shaped erosion trace on the outlet sidewall of the elbow may be related to secondary flow effects. The increase of the curvature ratio RD reduces the erosion intensity of the maximum erosion area, but subsequent increase will result in new secondary erosion trace near the outlet of the elbow and reach the maximum when RD = 8. Variations in particle size will have a significant effect on the extent of the erosion distribution, causing the main erosion distribution of the elbow to vary between 48.2° and 84.2°, while variations in pipeline diameter will have a lesser effect. The Stokes number can also be reduced by controlling the variation in particle size and pipe diameter to alter the force profile on the particles and reduce the erosion effect.